ANALISIS KESEHATAN KINERJA KEUANGAN BUMDes SUMBER MAKMUR DESA PAGAR MAYANG KECAMATAN TAMBUSAI UTARA - -, Hartini (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2016)
This study aims to analyze how Healthy Financial Performance BUMDes Pagar Mayang Sumber Makmur subdistrict North Tambusai. The method used in conducting research that is by using CAMEL. BUMDes increasingly rapid development in recent years, prompting the authors to conduct research on Health Analysis of the Financial Performance BUMDes. The types and sources of data used are secondary data obtained from the Financial Statements BUMDes Pagar Mayang village Sumber Makmur subdistrict North Tambusai over the last 5 years (end of period December 2011 s / d 2015). Data collection techniques used are in the documentation, interviews and systematic observation. Based on the results of research conducted on BUMDes Pagar Mayang village Sumber Makmur subdistrict North Tambusai using CAMEL method of analysis which in 2011 amounted to 96.96 is HEALTHY, 2012 amounted to 97.62 is HEALTHY, 2013 amounted to 93.72 is HEALTHY, 2014 at 77.23 is ENOUGH HEALTHY and 2015 amounted to 72.78 is HEALTHY ENOUGH. With the various shortcomings and limitations should BUMDes Sumber Makmur can improve their performance, in particular its financial performance in the coming years in order to be even better so as to increase public confidence Pagar Mayang. Companies are expected to increase cooperation both in doing work in the firms in order to create a good performance in the company.